Hubungan Prosedur Invasif dan Lama Rawat Inap Terhadap Kejadian Sepsis Neonatorum Awitan Lambat di RSUD Dr. H. Abdul Moeloek Tahun 2023 - Putri Arafah, Aisyah; Rukmono, Prambudi; Nareswari, Shinta; Saputra, Oktadoni (CV. Jasa Sukses Abadi, 2024)
Infant Mortality Rate (IMR) in Indonesia is still dominated by neonatal deaths, accounting for 55% of all infant deaths. Neonatal sepsis is the third leading cause of neonatal deaths after low birth weight (LBW) and asphyxia. Late-onset neonatal sepsis (LONS) is a systemic response to infection when the neonate is more than 72 hours old, as evidenced by a positive blood culture. Currently, late-onset neonatal sepsis remains the third leading cause of neonatal deaths. Late-onset neonatal sepsis usually occurs through the transmission of pathogens from the environment (nosocomial). The difficulty of early diagnosis in late-onset neonatal sepsis necessitates a diagnosis based on nosocomial infection factors, such as the use of invasive procedures and prolonged hospital stays. This research employed a descriptive analytic method with a cross-sectional approach. The sample consisted of all neonates diagnosed with neonatal sepsis and recorded in medical records with positive blood culture results in the Perinatology ward of RSUD Dr. H. Abdul Moeloek Bandar Lampung in 2023. Data were analyzed univariately and bivariately using the Chi-square test with Fisher's exact test as an alternative. The data suggests a statistically significant correlation between invasive procedures (p= 0.043) and length of hospital stay (p= 0.012) with the development of late-onset neonatal sepsis (LONS).